ANALYSIS OF STUDENT'S SELF-TRUST ASSESSED FROM THE INTENSITY OF USE OF INSTAGRAM SOCIAL MEDIA - Syifa Syamsuardi; Asmidir Ilyas (Universitas Negeri Padang, 2021)
Social media is the biggest platform used by students to present their own impressions. The social media that is quite widely used by students in Indonesia is Instagram. The use of Instagram social media has positive and negative impacts such as competition for luxury life, refusing to look at reality, and a crisis of confidence. In this case, one of the factors that is assumed to affect self-confidence is excessive use of social media Instagram. The purpose of this study was to see students' confidence in terms of the intensity of using Instagram social media. This study uses a comparative descriptive method with a quantitative approach. This study used a proportional random sampling technique with a sample size of 254 (n = 254). Data analysis used descriptive analysis and ANAVA test analysis using two way ANAVA. The findings of this study indicate that students' self-confidence is not significantly affected by the intensity of using Instagram social media.